Jamil Bashir’s Performance Style of Playing Oud by - Alwan, Raad Adnan (Journal of Tikrit University for Humanities, 2023)
Jamil Bashir was a prominent 20th-century oud player. He studied under Sharif Muhyiddin Haidar, who founded the Iraqi or Baghdadi oud school. This school's distinctive performing approaches elevated the oud from a singer's accompaniment to a solo instrument. This research examines Jamil Bashir's performing technique to developing new musical expression. This research advances academic knowledge by presenting a scientific investigation of Oud performing style. This research helps students and musicians explore Arabic music, especially Iraqi school performance practices. Within its theoretical framework, the research addressed two difficulties. The oud and the Sharif Muhyiddin Haidar school's role in Iraq's musical rebirth were the first topics. Performative and expressive mediations in oud playing were the second subject. Famous musician Jamil Bashir performed the piece under review. The research sought complete data and conclusions using a conventional technique. Jamil Bashir's work used performative mediations differently, according to the study. This shows the artist has a particular style from the start. This performance medium is employed in specific circumstances, unlike other mediums that have restricted or no use.